A Microstructure of the Modeling Systems on the Basis of the Fermented Raw Material - Vladimirovna, Zinina Oksana; Borisovich, Rebezov Maksim; Sergeevna, Vaiscrobova Evgeniya (Pakistan Journal of Nutrition, 2016)
A theoretical and practical interest to the expansion of the use of collagen containing raw material field in the meat foods production has been existing for many decades. But this raw material is notable in a technological respect for the unacceptable qualities that it is possible to improve by means of the biotechnological processing of the raw material. In recent years the propionic and bifidus bacteria have been drawing many scientists’ attention for the ferment processing conducting of the meat raw material. The propionic and bifidus bacteria have a high proteolytic activity and protective qualities in respect of the pathogenic and opportunistic pathogenic microflora. In this field scientists’ efforts are concentrated on the use of the mentioned bacteria in the production of fermented sausages or for the low-grade raw material softening. An aspect of using of the propionic and bifidus bacteria is studied not enough for the collagen containing raw material processing. Thereby the aim of the work is the study of the influence of the ferment processing of the collagen containing by-products of the 2nd category of bovine animals on the model systems micro structure, including protein compositions on the basis of the biomodificated by-products. In the study a detailed description of the change of the particular structural components of a model system is given when including to the model system the biomodificated raw material. It is established that under the influence of the ferment processing the decondensation of collagen fascicles occurs to particular fibrils and their fragmentation takes place. As a result when making protein compositions the homogeneous in structure emulsion comes out. Later on it is recommended to use the emulsion in boiled sausages and minced half-finished goods receipts.